Implementation of RC4 Cryptography Algorithm for Data File Security. (July 2020) - Doni, A F; Maria, O A H; Hanif, S
Abstract: Communication in the digital age plays an important role, a person can carry out various transactions or exchange data practically and quickly. So as to pose a great risk to information security, ranging from misuse of access or unauthorized authority, modification, change of information, destruction to theft, this is in accordance with the main principles of data and information security ranging from Confidentiality, Integrity, Authentication, and Availability. In research that has been done using RC4 Cryptography Algorithm for Encryption and Decryption in Data Files shows that the RC4 algorithm can run well and is able to secure the authenticity of the data so it is not easily changed by people who are not responsible or people who do not have good access rights in the form text or files in several pdf, doc, Docx, Xls, xlsx or text file formats and directly affect the execution time of encrypted and decrypted files.